Psoriatic arthritis and Hashimoto's thyroiditis in a patient presenting with major depression and subclinical hyperthyroidism: A case report - Lita Diah Rahmawati; Bagus Aulia Mahdi (Universitas Muhammadiyah Surabaya, 2024)
Psoriatic arthritis (PsA) is a chronic, deforming arthritis associated with psoriatic skin lesions. Numerous patients with PsA carry other co-existing chronic diseases, adding to their overall disease burden and affecting the patient’s quality of life. Depression is a common illness known to coexist in about 20% of patients with PsA. Long-term inflammation conditions can make patients more depressed and make the treatment more difficult. Cushing Syndrome (CS) is a complication of long-term treatment due to the exposure of glucocorticoids given to turn the hypothyroid condition into hyperthyroid because hypercortisolism in humans lowers TSH secretion and TSH pulse amplitude. When PsA combines with depression and CS, it will create complex conditions and treatments. The complexity is all about how we control the disease activity of PsA and the vicious circle of an inflammatory process that is difficult to control. Conventional treatment will fail, and targeted therapy with monoclonal antibodies such as anti-IL-17 Secukinumab, is needed. Secukinumab as an anti-IL-17 will block the inflammation pathway from interleukin-17, decrease the inflammation process, and improve the symptoms of PsA. We report a patient with psoriatic arthritis and Hashimoto's thyroiditis (HT) with a major depressive episode with CS and subclinical hyperthyroidism successfully treated with Secukinumab.